2012
DOI: 10.1111/jvim.12002
|View full text |Cite
|
Sign up to set email alerts
|

Milk Thistle and Its Derivative Compounds: A Review of Opportunities for Treatment of Liver Disease

Abstract: Milk thistle extracts have been used as a "liver tonic" for centuries. In recent years, silibinin, the active ingredient in milk thistle extracts, has been studied both in vitro and in vivo to evaluate the beneficial effects in hepatic disease. Silibinin increases antioxidant concentrations and improves outcomes in hepatic diseases resulting from oxidant injury. Silibinin treatment has been associated with protection against hepatic toxins, and also has resulted in decreased hepatic inflammation and fibrosis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
53
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(60 citation statements)
references
References 84 publications
(194 reference statements)
5
53
0
2
Order By: Relevance
“…Silibinin has a long history of safe use by humans, exhibiting extremely low toxicity [22]. Silibinin has been utilised as an effective treatment for hepatic disease [23] and as an adjunctive cancer therapy [24], [25].…”
Section: Introductionmentioning
confidence: 99%
“…Silibinin has a long history of safe use by humans, exhibiting extremely low toxicity [22]. Silibinin has been utilised as an effective treatment for hepatic disease [23] and as an adjunctive cancer therapy [24], [25].…”
Section: Introductionmentioning
confidence: 99%
“…Besides its strong hepatoprotective effect, silymarin exhibits anti-carcinogenic, antioxidant, iron chelating, anti-inflammatory, and immunomodulatory activities [12][13][14][15] . It has been recently reported that combination therapy of desferrioxamine and silymarin was more effective than desferrioxamine monotherapy in reducing iron burden 16 .…”
mentioning
confidence: 99%
“…Antioxidants commonly used to treat hepatobiliary disease in dogs include S‐adenosylmethionine, vitamin E, and silymarin (milk thistle extract). Silymarin also may inhibit hepatic fibrosis by decreasing HSC DNA synthesis, proliferation and migration, and decreasing hepatic collagen expression as well having anti‐inflammatory effects . Ursodeoxycholic acid is a nontoxic bile acid that has choleretic effects.…”
Section: Current Treatment Options For Hepatic Fibrosismentioning
confidence: 99%